Answers

2014-05-04T18:00:29+08:00
2. (4x + 1)(5x - 3)

                           4x + 1
                           5x - 3
                        - 12x - 3
                  20x2 + 5x
Answer: 20x2 - 7x -3

why?
(+ 1) (- 3) = negative 3
(- 3)(4x) = negative 12x
(5x)(+1) = positive 5x
(4x)(5x) = 20x squared

then?
1. bring down - 3
2. - 12x + 5 = - 7x
3. bring down 20x squuared


0
1. 2xy + 1 - xy + 3
answer: - 2xy2 + 5xy + 3 because......... (+3)(+1) = 3, (2xy)(3) = 6xy, (xy)(1) = 1xy, (2xy)(xy) = 2xy squared...